Implementation Analysis Of Participative Development In National Slum Upgrading Program [ KOTAKU ] - Agatha Christy Permata Sari; Agus Suman; David Kaluge (LPPM of NAROTAMA UNIVERSITY, 2018)
The phenomenon of slum settlements has been increasingly occurring in Indonesia. Slums are characterized by excessive population density which neglects its habitability. This program becomes one of the main agenda of Joko Widodo, the President of Indonesia, having a vision to alleviate slums, one of which is to implement the development program commonly known as National Slum Upgrading Program / KOTAKU. The program aims to create slum areas of 0% and is conducted in more than 100 districts in Indonesia. However, in its implementation, Sidoarjo regency becomes the public spotlight due to its development and achievement in economic growth improvement. This program is conducted in Sidoarjo supported by simultaneous the Regency Regulation enactment. Upon achieving success, Sidoarjo becomes a role model for other regions. Unfortunately, behind the success of development, there are two contradictory conditions, two slum villages having different development results since the development program was implemented in 2015. Bligo village becomes a successful village in establishing the development. Meanwhile, Jiken Village fails in achieving the expected development. Although the two villages share characteristics of being in adjacent location, conducting the same development program, and obtaining the same regional regulatory support, it is however not sufficient to support the success of development. This research is conducted by applying qualitative descriptive approach in order to obtain the result on the importance of participation in development process. The researchers apply the Eight Rungs of Citizen Participation, which can determine that Bligo village enters the stage of citizen control in which the community plays a full role in program implementation. Contrastingly, Jiken village only enters the stage of Informing, where the public only get information from the government related to development programs without any community empowerment. The participation of the community is crucial to the success of the development program. This is due to the existence of self-belonging exerting the ability to create sustainable development achievement.